Literature of an Independent England
XI, 253 p.
Keywords: Some of the most incisive writers on the subject rethink the relationship between Britain, England and English literary culture. It is premised on the importance of devolution, the uncertainty of the British union, the place of English Literature within the union, and the need for England to become a self-determining literary nation.